The genre of historical detective in contemporary European literature: peculiarities of functioning (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article definesthe feature of historical detective story that is unlike other genres of prose, the main pleasure for the reader –is, first, the intellectu-al component. It is noticed that fromthe top of the detective stands a chance to take a part in resolving an intellectual mystery, the entertainment from the text manifests itself as pleasure ofwhile solving puzzles. The authors combinemeta-physical atmosphere withadetective story, offering their own understanding of history.
Keywords: detective genre; intelligence